Public Communication in Smart Cities: A Bibliometric Analysis - Syahril; Achmad Nurmandi (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study scrutinizes the development of research on public communication in smart cities during the 2016–2024 period through a bibliometric approach. Drawing on bibliometric analysis, it identifies the mapping of publication trends, knowledge structures, thematic developments, and the transformation of research paradigms related to public communication within smart city studies. It shows that research on public communication in smart cities has grown significantly since 2016. Early studies were primarily dominated by themes related to information and communication technologies (ICT), the Internet of Things (IoT), big data, digital platforms, and smart governance systems. Over time, research trends shifted toward issues of citizen participation, transparency, digital inclusion, sustainability, privacy, cybersecurity, and ethical governance. The bibliometric analysis also reveals that the United States, China, and the United Kingdom are the countries with the highest publication contributions. Furthermore, the thematic synthesis identified five major research clusters: Digital Communication Infrastructure, Smart Governance and Citizen Participation, Sustainability and Urban Communication, Security and Privacy, and Human-Centered Smart Cities. This study confirms that public communication in smart cities is no longer limited to the dissemination of digital information but has evolved into a multidimensional governance approach that integrates citizen engagement, transparency, sustainability, digital ethics, and participatory communication within the broader framework of smart urban transformation.